The competition grid : experimenting with & within architecture competitions - Theodorou, Maria; Katsakou, Antigoni (RIBA Publishing, 2018)
The Competition Grid: Experimenting With and Within Architecture Competitions is a comprehensive review of architectural competitions. Each section features international research overviews as well as lively discussions with experts that draw on first-hand experience of the competition process.